Franchising as a strategy for job creation in the clothing sector: A case study of Walvis Bay - Shitemba , Kristina; Onojaefe , Darlington Peter; Kasse, Sophie Nguepi; Ukpere, Wilfred (Journal of Economic Development, Environment and People, 2022)
The franchise business model enjoys much support in both developed and developing countries. It is considered by many as a key contributor to economic growth and is also perceived as a vital vehicle for job creation. Unemployment rates in Namibia are currently a cause for concern and approaches are needed to stimulate job creation. This study reports on perceptions of franchising as a job creation strategy within the Walvis Bay area. The study employed a mixed method research design and used a survey questionnaire and semi-structured interviews to collect data. A total sample of n=110 completed the questionnaire, while n=6 participants were interviewed. The study results indicate a rapid growth and awareness of the franchise model in the food sector, while less growth was evident in the clothing sector. The franchise model was however, seen as a key avenue for stimulating economic growth and viable job creation strategy. Stronger incentivization is recommended, specifically in the areas of tax exemptions, export processing zones, introduction of specific franchise legislation and more expansive monetary and fiscal policies.